Bermain Sebagai Upaya Dini Menanamkan Aspek Sosial Bagi Siswa Sekolah Dasar - Nurhayati Simatupang (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Playing is the main need for children. During the playing process, childrenwould develop and change physically, mentally and their social aspect.As the technology development grows recently, the implication of this matter is changedin chosing to the from of activity of children playing. For this moment many childrenchoosen to play with electronical thing. The consequences of this, they ownlessinteraction among other children.Those play programmed and systemized based on material teaching that they couldincrease the better value in the early social aspect developing systemKata Kunci: Bermain, Aspek Sosial.